Syrian Immigrants in Germany: An Exploration into Intercultural Competence, Self-awareness and Well-being of the Minority Group - Hateem Al Khuja; Björkqvist, Kaj (Technium Social Sciences Journal, 2020)
The intercultural competence of Syrians who reside in Germany was assessed in order to shed light on patterns and behaviours that are practiced by them in a different culture. In total, 308 respondents completed the questionnaire, of which 54 (17.5%) were female and 254 (82.5%) were male. The mean age of the respondents was 30.5 years (SD = 7.5.). The respondents’ level of private self-awareness, particularly self-reflection and insight, and their level of well-being (depression, anxiety and aggression) were assessed. Intercultural competence was measured using APTOC, a 15-item scale that consists of 3 main subscales, namely Openness to Other Cultures, Global Mindset, and Narrow Mindset. Private self-awareness was measured with the Self-reflection and Insight Scale. Well-being was measured with three subscales of the Brief Symptom Inventory, namely Depression, Anxiety and Hostility. Openness to other Cultures, Global Mindset and Narrow Mindset were found to have a significant impact on Self-reflection and the well-being determinants (except Anxiety). There was a significant negative correlation between Narrow Mindset and Insight. Conclusively, Intercultural competence was found to have a positive impact on Private Self-awareness (Self-reflection and Insight) and Well-being of Syrians who reside in Germany.